Enigmatic Headstands in European Freshwater Fish Species - Michal Tušer; Jaroslava Frouzová (Ecology and Evolution, 2025)
ABSTRACT This study discloses a remarkable and rarely documented behavior among two cyprinid species—the common bleak (Alburnus alburnus) and the common roach (Rutilus rutilus)—and one percid species, the European perch (Perca fluviatilis). The primary aim was to reevaluate this distinct behavior, termed “headstand”, and explore its potential implications for fish behavior and ecology. We utilized video recording to observe and analyze this behavior. Fish were monitored in an enclosure with near‐natural conditions. Instances of headstanding behavior—where fish assume a head‐down posture at angles between 45° and 90°—were documented. The video analysis revealed the occurrence of headstanding behavior in all three species, lasting from a few seconds to over a minute. This behavior was observed both individually and in groups, sometimes involving multiple species simultaneously. Group headstands occurred more frequently in the year when water transparency was low. Interestingly, although this behavior was previously proposed as a cleaning signal, no cleaning activity was observed afterward. Our observations suggest that headstanding may serve additional functions beyond a cleaning context, potentially involving foraging, predator avoidance, or social communication. Observing this behavior under diverse conditions highlights its ecological and social relevance. Future work integrating behavioral, ecological, and physiological approaches could clarify the adaptive significance of headstanding employed by these species.